Effects of Nanoscale Ripple Texture on Friction and Film Thickness in EHL Contacts - Woloszynski, Tomasz; Touche, T.; Podsiadlo, Pawel; Stachowiak, Gwidon; Cayer-Barrioz, J.; Mazuyer, D. (Springer, 2019)
The effects of nanoscale ripple texture on the film thickness and friction in elastohydrodynamically lubricated (EHL) contacts were investigated through ball-on-disc experiments and numerical simulations of line contacts. The texturing was produced by femtosecond LASER irradiations and the ripple texture was in the form of sinusoidal waviness with nanoscale amplitudes and wavelengths. The experimental and numerical results indicate that the orientation of the ripples with respect to the entrainment direction has little to no effect on their capability to form a lubricating film. In the EHL regime, the ripples were found to reduce the central and minimum film thickness by half of their peak-to-peak amplitude as compared to a smooth contact. The transition from EHL to mixed lubrication regime was attributed to micro-EHL effects although the subsequent friction increase was found to be largely due to the onset of asperity contacts. In the mixed lubrication regime, the coefficient of friction was mainly determined by surface roughness and its value increased with an increase in the ripple amplitude.